2015
DOI: 10.2174/1567202612666150731110247
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes in the Methylation Patterns of KCNQ1 and WT1 after a Weight Loss Intervention Program in Obese Stroke Patients

Abstract: Ischemic stroke patients often show high concentrations of circulating inflammatory markers that are associated with increased risk of recurrence. Epigenetic mechanisms could be involved in obesity, inflammation and stroke. The objective of this research was to investigate, in obese patients suffering a previous stroke, the effects of a nutritional program on anthropometric and biochemical variables, and on the methylation patterns of two stroke-related genes (KCNQ1: potassium channel, voltage gated KQT-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The MENA cohort is constituted by previous clinical trials analyzing genome‐environmental interactions concerning weight management and associated metabolic outcomes (Abete et al., 2015; Huerta, Navas‐Carretero, Prieto‐Hontoria, Martínez, & Moreno‐Aliaga, 2015; Larsen et al., 2010; Martínez‐González et al., 2014; Petersen et al., 2006; San‐Cristobal et al., 2015; Santos et al., 2016; Zulet et al., 2011). Each study received ethical approval from appropriate local Human Research Ethics Committees.…”
Section: Methodsmentioning
confidence: 99%
“…The MENA cohort is constituted by previous clinical trials analyzing genome‐environmental interactions concerning weight management and associated metabolic outcomes (Abete et al., 2015; Huerta, Navas‐Carretero, Prieto‐Hontoria, Martínez, & Moreno‐Aliaga, 2015; Larsen et al., 2010; Martínez‐González et al., 2014; Petersen et al., 2006; San‐Cristobal et al., 2015; Santos et al., 2016; Zulet et al., 2011). Each study received ethical approval from appropriate local Human Research Ethics Committees.…”
Section: Methodsmentioning
confidence: 99%
“…Seven diet studies [17,18,[21][22][23][24][25], and all three GBP [29][30][31] studies measured preversus postintervention changes in DNAm to explore mechanisms of epigenetic remodeling in response to weight loss (hereafter referred to as 'mechanistic studies'). Overall, these mechanistic studies provide evidence that weight loss affects the methylation status of several genes, including obesity-associated genes (FTO, BDNF, SH2B1, PPARGC1A, PDK4, IL1B, SERPINE1 [16,21,29,31,41]), metabolic genes (SCD1 [22], PON1 [25]), stroke-related genes (KCNQ1 and WT1 [17]), genes regulated by diet (FADS1, FFAR3, CD14-36 [18]) and circadian rhythm genes (CLOCK, PER2, BMAL1 and NR1D1 [23][24]). The changes in the methylation of these genes in response to weight loss may reflect the reversal of epigenetic modifications that either cause or are caused by obesity.…”
Section: Candidate-gene Approach Studiesmentioning
confidence: 99%
“…However, higher levels of baseline methylation of SERPINE-1 were associated with opposite weight loss outcomes in the two studies: with a greater weight loss in response to a calorie-restricted diet, and with lower weight loss after GBP surgery. Finally, discrepant results were found for the gene PDK4, whose methylafuture science group Systematic Review Aronica, Levine, Brennan et al [17] Calorie-restricted diet with or without fish oil supplementation by weight loss but not by fish oil supplementation [18] Calorie restriction diet/8 weeks Obese women (n = 12) and obese men (n = 12) PBMC Bisulfite sequencing TNF-α Lower baseline levels of total TNF-α promoter (from -360 to +50 bp) methylation (r = 0.778, p = 0.014), especially in the positions 170 bp (r = 0.808, p = 0.001) and 120 bp (r = 0.673, p = 0.021), in obese men with successful weight loss (≥5% of initial body weight) [19] Calorie restriction diet)/8 weeks (-245 and -239 CpGs, 39%, p = 0.071) than the nonresponder group (n = 6), while no differences were found between responder and nonresponder group in LEP and TNF-α gene expression [16] Calorie restriction diet)/8 weeks with follow-up 32 weeks later Obese men (n = 18), who regained (regainers; n = 7) or not (nonregainers; n = 11) more than 10% of the weight lost after the intervention PBL MassArray EpiTyper POMC NPY Regainers showed higher methylation levels at CpG sites +136 and +138 bp within POMC (+26%; p = 0.020) and lower methylation of NPY (28 CpGs within a region spanning from -211 to -646 bp with respect to the transcription start site; -22%; p = 0.033) compared with nonregainers. Total baseline NPY methylation was associated with weight regain (r = -0.76; p < 0.001) [20] Calorie restriction = -0.403, p = 0.002), body weight change (r 2 = 0.421, p = 0.004) and body weight, change in body weight and truncal fat mass reduction (CC vs TT + CT genotypes, p < 0.05), respectively [21] ATP10A: ATPase phospholipid transporting 10A; BDNF: Brain-derived neurotrophic factor; BMAL1: Brain and Muscle ARNT-Like 1; CD14-36: Cluster of differentiation gene was selected for analysis) SERPINE1 Assessed baseline methylation (>7%) of CpG 10 in the SERPINE1 promoter (All CpGs were from -1408 to +113 bp).…”
Section: Candidate-gene Approach Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Campion et al (72) and Cordero et al (73) demonstrated in peripheral blood mononuclear cells and in subcutaneous adipose tissue, respectively, that before a weight loss intervention, several cytosine and guanine separated by only one phosphate (CpG) sites located in the promoter region of tumor necrosis factor a (TNFA) and LEP were hypomethylated in those subjects with greater response to the calorie restriction intervention. Another study observed that a body weight loss program based on the Mediterranean diet significantly reduced the total methylation levels of potassium channel, voltage-gated KQT-like subfamily Q, member 1 (KCNQ1) and Wilms tumor 1 (WT1) (74).…”
Section: Epigeneticsmentioning
confidence: 99%